Effect of replacing traditional ingredients for oils and flours from nuts and seeds on the characteristics and consumer preferences of lamb meat burgers - Rabadán, A.; Álvarez-Ortí, M.; Martínez, E.; Pardo-Giménez, A.; Zied, D. C. [UNESP]; Pardo, J. E. (Elsevier, 2021)
Processed products elaborated using red meats are considered as unhealthy and rejections from health-conscientious consumers are increasing. In this regard, the aim of this study is to reformulate traditional lamb burgers replacing partially or totally the lamb meat, the lamb fat and the thickener (corn starch) by oils and flours from different seeds and nuts. Physical parameters, proximate analysis and consumer evaluation of the reformulated burgers were analyzed. By partially replacing lamb meat by defatted almond flour an increase in the protein concentration of burgers (p < 0.05), with similar energy values, was observed. Burgers samples produced using chia and poppy defatted flours resulted in low-calorie burgers with higher carbohydrate content (p < 0.05). The study suggest that the use of seeds and nuts oils and flours results in burgers with similar physical properties and consumer preference that the traditional burgers, but with improved health benefits that would encourage consumption. Consumer segmentation using the Food Neophobia Scale suggests that non-neophobic consumers were those that showed higher preference for most of the novel burgers. Novel healthier burgers would receiver further acceptance when aimed to this specific consumer segment.
Keywords: Consumer preference; Food neophobia; Food reformulation; Processed meat; Red meat